(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
In the effort of a surgeon to overcome in the best possible way a difficult surgical event such as the removal of tumors from liver, it is required the use of all possible imaging-diagnostic tools to familiarize the doctor with the current patient’s situation. Even though tomography images are implying the 3D geometry of the human body they are not providing in a manageable way specific 3D model structures of separate organs. The present work concerns the use of 3D modeling techniques to produce 3D physical model of both liver and its internal geometry (vessels, tumor) using a 3D printer.